The Val66Met coding variant of the brain-derived neurotrophic factor (BDNF) gene does not contribute toward variation in the personality trait neuroticism. - Willis-Owen, SA; Fullerton, J; Surtees, P; Wainwright, N; Miller, S; Flint, J (2005)
BACKGROUND: The val66met variant located within the brain-derived neurotrophic factor gene (BDNF) has previously been associated with human neuroticism, a dimension of personality strongly predictive of depressive illness. METHODS: Here we report an attempt to replicate this association using three populations of extreme neuroticism scorers derived from two large English cohorts (n = 88,142 and n = 20,921). On the basis of the current literature, which indicates that an effect of BDNF may only become apparent in those individuals exposed to stress, a gene-environment interaction was also sought. RESULTS: No statistically significant effects were identified, although simulations indicated that the samples held sufficient power to detect a main effect accounting for just .75% of variation and an interaction accounting for 4% of variation. CONCLUSIONS: These data do not support the hypothesis that the val66met BDNF polymorphism contributes toward variation in the human personality trait neuroticism, at least as indexed by the Eysenck Personality Questionnaire.